Ruth Bush. Publishing Africa in French: Literary Institutions and Decolonization, 1945-1967. Liverpool UP, 2016. - Madeline Bedecarre (Studies in 20th & 21st Century Literature, 2018)
Review of Ruth Bush. Publishing Africa in French: Literary Institutions and Decolonization, 1945-1967. Liverpool UP, 2016. 224 pp.
Keywords: Ruth Bush; publishing; Africa; French; literary institutions; decolonization